2022
DOI: 10.3389/fmicb.2022.864198
|View full text |Cite
|
Sign up to set email alerts
|

Six New Species of Tomentella (Thelephorales, Basidiomycota) From Tropical Pine Forests in Central Vietnam

Abstract: Up to this point, studies on the taxonomy and phylogeny of the basidiomycetous genus Tomentella stemmed mainly from the temperate to boreal zones of the Northern hemisphere but were scarce in tropical Asia. In this study, six new species—T. bidoupensis, T. brevisterigmata, T. cinereobrunnea, T. longiechinula, T. stipitobasidia, and T. verruculata from central Vietnam in Southeast Asia—are described and illustrated on the basis of morphological characteristics and molecular phylogenetic analyses of the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…A similar topology was obtained using ML and Bayesian analyses with one sample of Odontia ferruginea as the outgroup [65], and only the ML tree is shown in Figure 1 with the ML bootstrap values and Bayesian posterior probabilities. In the phylogenetic tree, 18 clades with moderate to strong support were marked, of which six clades (clade 2, 4, 6, 8, 10 and 16) were consistent with the previous ITS + LSU phylogenetic analyses [65].…”
Section: Phylogenetic Analysesmentioning
confidence: 55%
“…A similar topology was obtained using ML and Bayesian analyses with one sample of Odontia ferruginea as the outgroup [65], and only the ML tree is shown in Figure 1 with the ML bootstrap values and Bayesian posterior probabilities. In the phylogenetic tree, 18 clades with moderate to strong support were marked, of which six clades (clade 2, 4, 6, 8, 10 and 16) were consistent with the previous ITS + LSU phylogenetic analyses [65].…”
Section: Phylogenetic Analysesmentioning
confidence: 55%
“…The Byssocorticium and Inocybe fungi are highly competitive in harsh environments, occupying dominant positions [48], with the former possessing saprotrophic functions, facilitating nutrient cycling in plants by decomposing forest litter [49], and the latter supplying host plants with water and mineral nutrients, playing a crucial ecological role in forest succession [50]. Species in the Tomentella genus are known to form ectomycorrhizae (ECM) with higher plants, absorbing host carbohydrates while supplying nitrogen and water, a symbiotic relationship critical for forest ecosystem succession and biodiversity maintenance [51]. In the case of Phaeocollybia, one study has suggested a root parasitic lifestyle [52], whereas recent work from Abies forests in Mexico suggested that Phaeocollybia is ECM [53].…”
Section: (A) (B)mentioning
confidence: 99%
“…Generally, species of Thelephora contain a variety of shapes of basidiocarps and basidiospores with tuberculate or echinulate ornamentation, which help differentiate it from other genera in Thelephoraceae. Nevertheless, molecular validations have confirmed that Thelephora and Tomentella have a very close genetic relationship on the phylogenetic tree; the two genera are usually intermixed in the same evolutionary branch and do not form separate monophyletic groups (Vizzini et al, 2016 ; Lu et al, 2022 ). Furthermore, some species of the two genera have similar microscopic characteristics, such as tuberculate or echinulate ornamentation, and the same size and form as basidiospores (Stalpers, 1993 ; Lee et al, 2010 ; Yorou et al, 2011 ; Ramírez-López et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some species of the two genera have similar microscopic characteristics, such as tuberculate or echinulate ornamentation, and the same size and form as basidiospores (Stalpers, 1993 ; Lee et al, 2010 ; Yorou et al, 2011 ; Ramírez-López et al, 2015 ). The subtle classification boundary of the two genera has been controversial and still remains unresolved (Ramírez-López et al, 2015 ; Li et al, 2020 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation